Success despite starting out at a disadvantage: What helps second-generation migrants in France and Germany? - Ingrid Tucci; Ariane Jossin; Carsten Keller; Olaf Groh-Samberg (DIW Economic Bulletin, 2011)
The educational and employment trajectories of migrant children in France and Germany are extremely diverse. The few successful ones dominate the public eye. Yet successful biographies of young adults with a migration background are in no way a negligible exception. However, the picture is different in the two countries: while in France more migrants' descendants manage to reach their (secondary?) general qualification for university entrance in Germany they are overrepresented particularly at the Hauptschule (general secondary school). It is, however, considerably more difficult for these young people in France to gain a long-term foothold in the labor market, while in Germany they often take the chance to acquire a vocational qualification and have better job opportunities. As part of a three-year research project, the question examined was which social and institutional factors can stabilize educational attainment and professional orientation. On the basis of qualitative interviews, which were conducted with young adults with a migration background in four disadvantaged areas of Berlin and Paris, it is possible to name three factors that play an important role in the success and/or the stabilization of early educational and employment trajectories: the support provided by significant third parties, entry into milieus which are more socially and culturally diverse, and the prospect of a second chance.
Keywords: J15; I24; J21; 330; migration; integration; second generation; education; labor market; trajectories